Syrian refugees and the politics of migration in Europe :|an ontological security perspective - Albayrak, Bahar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis examines the effects of the mass arrival of Syrian refugees to European politics by using the concept of ontological security. It focuses on the identity dimension of the issue by depicting the relationship between ontological security and the anti-refugee discourse and policies of states. The main argument of the thesis is as follows: the reason for the rise of anti-refugee discourse and the policies of exclusion of refugees is the sense of disruption in ontological security. Two states, Germany and Hungary, are used as case studies within the period between 2015 and 2017. The research collects data from sources through the literature based on the concept of ontological security to establish the theoretical framework of the thesis; media outlets to make a discourse analysis of declarations, interviews and party programs of political actors and; the examination of legal documents and political developments to determine the exclusion methods of states. In the discursive realm, the thesis identifies three main themes in the discourse producing process in case countries. In the exclusionary realm, the thesis examines two types of exclusion: physical and legal. The thesis intends to indicate that the ontological insecurity arising from the mass arrival of Syrian refugees brings the same conclusion even in two different countries, Hungary and Germany: anti-refugee discourse and policies.
Keywords: Refugees -- Government policy -- Europe.; Refugees -- Syria -- Europe.